Hydrothermal Carbons from Hemicellulose-Derived Aqueous Hydrolysis Products as Electrode Materials for Supercapacitors - Falco, Camillo (2013)
Acid pretreatment of lignocellulosic biomass, required for bioethanol production, generates large amounts of by-products, such as lignin and hydrolyzed hemicellulose fractions, which have found so far very limited applications. In this work, we demonstrate how the recovered hemicellulose hydrolysis products can be effectively utilized as a precursor for the synthesis of functional carbon materials through hydrothermal carbonization (HTC). The morphology and chemical structure of the synthesized HTC carbons are thoroughly characterized to highlight their similarities with glucose-derived HTC carbons. Furthermore, two routes for introducing porosity within the HTC carbon structure are presented: i) silica nanoparticle hard-templating, which is shown to be a viable method for the synthesis of carbonaceous hollow spheres; and ii) KOH chemical activation. The synthesized activated carbons (ACs) show an extremely high porosity (pore volume≈1.0 cm3 g−1) mostly composed of micropores (90 % of total pore volume). Because of their favorable textural properties, the ACs are further tested as electrodes for supercapacitors, yielding very promising results (300 F g−1 at 250 mA g−1) and confirming the high suitability of KOH-activated HTC carbons derived from spruce and corncob hydrolysis products as materials for electric double layer supercapacitors.